Midflexion Instability in Primary Total Knee Arthroplasty - Nagle, Matthew; Glynn, Aaron (The Journal of Knee Surgery, 2020)
Instability is one of the most common causes of failure in total knee arthroplasty. Traditionally, it has been classified into three types: extension instability, flexion instability, and hyperextension instability. More recently, a fourth type of instability has been proposed, namely “midflexion instability” (MFI). Whether MFI is distinct from the aforementioned types of instability is contentious, and at present, the condition is yet to be clearly defined. This article reviews the current literature and identifies the best available evidence relevant to the concept of MFI. Our aim is to present an overview of the proposed causes and mechanisms for MFI. By doing so, we also aim to provide a focus on how MFI presents, whether it is indeed a discrete form of instability, and if it influences clinical results.
Keywords: midflexion; total knee arthroplasty; modes of failure; instability